IMPLEMENTASI ETIKA BISNIS ISLAM PADA PEDAGANG KULINER DI TAMAN ALUN PUTUSSIBAU KLIMANTAN BARAT - Jumratul Hasanah; Beni Supriadi (BORJUIS: JURNAL OF ECONOMY, 2023)
This research is motivated by the lack of organized waste management in Taman Alun Putussibau which comes from food and drink packaging from culinary traders in Taman Alun Putussibau. The research focuses on finding out and analyzing about How to implement Islamic business ethics among culinary traders in Taman Alun Putussibau. 2). What are the obstacles faced by culinary traders in Taman Alun Putussibau in implementing Islamic business ethics and 3). What is the impact of the implementation of Islamic business ethics on culinary traders in Taman Alun Putussibau. This research uses a qualitative approach with the type of field The subjects of this research were culinary traders in Alun Putussibau park, namely food and drink traders. Data sources consist of primary data and secondary data with data collection techniques using interviews, observation and documentation. Data analysis techniques using data collection, data reduction, data display and drawing conclusions. The technique for checking the validity of the data used is the credibility test, including diligent observation, member checking and method triangulation. then transferability test, reliability test, and objectivity test. The research results show that 1). Culinary traders in Taman Alun Putussibau are able to implement 3 aspects of the Islamic business axioms, namely balance, free will and responsibility, but have not been able to implement the unity aspect. The obstacle faced by culinary traders in implementing Islamic business ethics is that they prioritize trading rather than carrying out their obligations as a Muslim. Apart from that, there are obstacles in terms of poor waste management regulations, so it is hoped that there will be good cooperation between culinary traders, buyers and the relevant government. 3). The impact of implementing Islamic business ethics on culinary traders in Taman Alun Putussibau is to increase education about the importance of trading based on Islamic business ethics so that culinary traders can communicate well and in accordance with Islamic law